2009
DOI: 10.1039/b817064a
|View full text |Cite
|
Sign up to set email alerts
|

Potentiometric sensing of butyrylcholinesterase based on in situ generation and detection of substrates

Abstract: A novel reagentless biosensor has been developed in which the traditional ion selective electrode is used as a controlled-release system for in situ generation and detection of enzyme substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

7
1

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…23 In our previous research, we found that the outward ion fluxes of substrate ions across an ISE membrane could be used for potentiometric biosensing of enzymes and their inhibitors. 24 This strategy does not require the addition of substrate ions to the sample solution. The substrate ions released at the sample−membrane interface can be controlled and modulated precisely by using an external current.…”
Section: Introductionmentioning
confidence: 99%
“…23 In our previous research, we found that the outward ion fluxes of substrate ions across an ISE membrane could be used for potentiometric biosensing of enzymes and their inhibitors. 24 This strategy does not require the addition of substrate ions to the sample solution. The substrate ions released at the sample−membrane interface can be controlled and modulated precisely by using an external current.…”
Section: Introductionmentioning
confidence: 99%
“…fluxes in the direction of the sample solution) has been developed for measuring a wide range of analytes which can decrease the concentrations of the indicator ions released at the samplemembrane phase boundary via complexing [17], redox [18] or enzyme-catalyzed reactions [19][20][21]. Such an ISE membrane not only serves as a polymer matrix for reagent release, but also works as a transducer for sensitive potentiometric detection, making the ISE membrane very attractive for sensor miniaturization.…”
Section: Introductionmentioning
confidence: 99%
“…9 This system can be used as a simple and effective potentiometric biosensor based on disturbance of transmembrane diffusion fluxes of ion-selective electrodes under near-zero-current conditions. Such an ISE membrane not only serves as a polymer matrix for reagent release but also works as a transducer for sensitive potentiometric detection, making the ISE membrane very attractive for sensor miniaturization.…”
mentioning
confidence: 99%
“…In addition to the conventional ingredients, 9 ETH 500 was incorporated into the ISE membrane. This lipophilic electrolyte was used to decrease the membrane resistance and thereby the IR voltage drop inside the currentpolarized membrane.…”
mentioning
confidence: 99%